In vitro evaluation of microleakage at implant-abutment interface in three different implant systems using dye penetration technique - Mostafa Khani; Farshad Bajoghli; Ehsan Ghasemi; Mahmoud Sabouhi; Majid Boozari; Sayed Mahdi Ghasemi (Isfahan University of Medical Sciences, 2013)
Introduction: Precise fit between implant components is an important factor for successful implant treatment. The aim of this study was to determine microleakage of Biohorizons, Implantium and Swiss Plus implant systems.Materials and Methods: In this experimental study, 5 implant fixtures from 3 implant systems were subjected to dye penetration test. One µL of 0.1% Toluidine blue solution was injected into implant fixtures using an electronic pipette. The corresponding abutments were subsequently screwed onto the implants with a torque of 30 N. Implant‒abutment complexes were placed in 2 mL of distilled water. The amount of leakage of Toluidine blue (TB) was measured by a spectrophotometer at 630 nm at 1-, 3-, 6-, 24-, 48-, 72-, 96-, 144-, 192- and 240-hour intervals after incubation. Calibration curve and a linear equation were obtained by Excel software. Data were analyzed with SPSS 11.5 using ANOVA (α = 0.05).Results: In the three implant systems evaluated microleakage was only statistically significant at hours 1 (p value = 0.01), 3 (p value = 0.011) and 6 (p value = 0.000). Two-by-two comparisons between the implant systems during the first three hours showed the highest microleakage with Swiss Plus and the least microleakage with Implantium systems. However, after the first three hours the differences were not statistically significant between the three implant systems.Conclusion: Among the three implant systems evaluated the least and highest microleakage scores at 1-, 3- and 6-hour intervals were observed with the Implantium and Swiss Plus systems, respectively. All the implant systems exhibited microleakage with time. Key words: Dental implant‒abutment connection, microleakage, spectrophotometry